Contribuições do Pensamento Computacional para o Ensino e aprendizado de Língua Portuguesa - Alexandre Nascimento, Carlos; Abdalla dos Santos, Débora; Tanzi Neto, Adolfo (RENOTE, 2018)
This study aimed to investigate possible contributions of Computational Thinking for the Teaching and Learning Portuguese Language in Basic Education. Interventions were carried out in the teaching of Portuguese Language content through didactic sequences that included the association of the subject to Computer Science. The data collected, through focus groups, interviews and diaries were evaluated qualitatively based on the literature. Based on the results obtained, there are indications that the integration between the Computational Thinking skills and the indexes explored during the Portuguese Language classes is possible and that they are integrated in teaching and learning.